METHOD OF ESTIMATION FREQUENCY PROPERTIES OF THE PREINSULATED PIPES FOR MONITORING THE STATUS OF HEATING NETWORKS - E. N. Taletskiy (Приборы и методы измерений, 2015)
Proposed approximate method for the preliminary assessment of the frequency properties unadapted guiding system for monitoring the status of the organization of preinsulated pipes. Guide system elements  formed  tubes  placed  in  a  lossy  medium  (soil).  A  theoretical  analysis  shows  the  frequency dependence of the propagation constant components: the damping coefficient and the phase coefficient, take advantage of these characteristics of the system for monitoring the status heating networks.